Spontaneous coronary artery dissection and atherosclerosis in a young man with systemic lupus erythematosus: A case report and literature review - Huang, Hongbo; Ma, Xiaojuan; Xu, Linjie; Wang, Xin; Shi, Dazhuo; Zhao, Fuhai; Zhang, Ying (Frontiers in Cardiovascular Medicine, 2022)
Background Spontaneous coronary artery dissection (SCAD) is a rare coronary artery disease that frequently occurs in young, female patients without risk factors, and conservative treatment is often recommended for its management. The patient reported here is a male patient with systemic lupus erythematosus (SLE). Case summary We described a 28-year-old man with SLE who presented with acute ST-segment elevation myocardial infarction (STEMI), and was diagnosed with SCAD through a long dissection of the left anterior descending branch (LAD) by coronary angiography. The patient was treated with percutaneous coronary intervention (PCI) with stent implantation. Ten years later, he developed in-stent stenosis and other coronary atherosclerosis and was retreated with PCIs. Based on this case and according to the literature review, the existing treatment and prognosis of SLE with spontaneous coronary artery dissection and atherosclerosis are discussed. Conclusion Cardiovascular complications should be considered in patients with systemic lupus erythematosus, although they may not initially be atherosclerotic diseases. Attention should be paid to distinguish spontaneous coronary dissection in order to minimize missed or delayed diagnoses and take appropriate managements, as well as the development of atherosclerosis in SLE patients, and timely intervention has a better prognosis.